Conflicts and alternative mechanisms in displaced communities from Quibdó (Chocó-Colombia) - Cuesta Cuesta, Doris (DIXI, 2013)
We aimed to ref lect, by means of surveys and interviews, both the conf licts of, and the mechanisms employed by, the displaced communities of Quibdó, as well as their socioeconomic characterization. The results allow us to propose alternative mechanisms for conf lict resolution that may foster a peaceful cohabitation in this depressed zone of the country.